Comprehensive data collection for the development of anchorage lifetime prediction models. Issue 2 (22nd April 2019) - Wan‐Wendner, Roman; Czernuschka, Lisa‐Marie; Boumakis, Ioannis; Ninčević, Krešimir
Abstract: Nowadays, fastening systems represent a very important part of the construction industry due to their versatility and use in reconstruction. Therefore, it is essential to study and understand phenomena and effects influencing the lifetime of a fastening system. However, the mechanisms are complex and not yet fully understood. As a result, numerical models, which are reliable and are able to capture all involved effects, are needed. The basis of these models is a wide range of high quality data, for model development, calibration, and validation purposes. Within the 7‐year Christian Doppler Laboratory (CDL) of Life Cycle Robustness, an extensive concrete data base, consisting of short‐term mechanical properties of concrete, time‐dependent measurements as well as tests on full fastening systems, was generated. The material tests reach from compression, indirect tensile, and fracture tests to long‐term creep and shrinkage tests. Shear and pull‐out tests were carried out on bonded and mechanical anchors. In order to characterize the long‐term performance, sustained load and time to failure tests were conducted at a system level. In total, 12 concrete mixes were tested. This contribution will give an overview of the performed tests and will highlight the importance of sound experimental data.